2021
DOI: 10.14423/smj.0000000000001320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gestational Weight Gain on Delivery Outcomes in an Obese, Low-Income Population

Abstract: Objective: To examine the effects of weight gain/loss on delivery outcomes stratified by class of obesity in an obese, low-income, predominantly minority population.Methods: A retrospective review of a cohort of 1428 women receiving care at a large Medicaid clinic from 2013 to 2016 with pregravid body mass index ≥30 was conducted. Multinomial logistic regression analysis was used to compare differences in gestational weight change to the primary outcomes of birth-weight percentile and delivery type and seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Following the removal of duplicates, 684 titles and abstracts were screened. Eighty-three studies were selected for full-text review, and 29 studies [ 8 , 16 , 17 , 20 45 ], involving 1242420 obese pregnancies, met our eligibility criteria and were included in the systematic review. The kappa coefficient of agreement for included studies between the reviewers (LJ and LBY) was 0.99.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following the removal of duplicates, 684 titles and abstracts were screened. Eighty-three studies were selected for full-text review, and 29 studies [ 8 , 16 , 17 , 20 45 ], involving 1242420 obese pregnancies, met our eligibility criteria and were included in the systematic review. The kappa coefficient of agreement for included studies between the reviewers (LJ and LBY) was 0.99.…”
Section: Resultsmentioning
confidence: 99%
“…We got 29 articles [ 8 , 16 , 17 , 20 45 ] including prospective [ 17 , 29 ] and retrospective cohort studies [ 8 , 16 , 20 28 , 30 45 ], built into our meta-analysis. The included studies reported on at least 1242420 obese pregnant women.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations